Maintenance of zilucoplan efficacy in patients with generalised myasthenia gravis up to 24 weeks: a model-informed analysis - Guillemette de la Borderie; Damien Chimits; Babak Boroojerdi; Melissa Brock; Petra W. Duda; Fiona Grimson; Paul Mahoney; Foteini Strimenopoulou; Gary Cutter; Inmaculada Aban; Susanna Brauner; Malin Petersson; et al. (Therapeutic Advances in Neurological Disorders, 2024)
Background: Clinical efficacy of zilucoplan has been demonstrated in a 12-week, placebo-controlled, phase III study in patients with acetylcholine receptor autoantibody-positive generalised myasthenia gravis (gMG). However, placebo-controlled zilucoplan data past 12 weeks are not available. Objectives: Predict the treatment effect of zilucoplan versus control (placebo or standard of care) in patients with gMG up to 24 weeks. Design: A model-informed analysis (MIA) within a Bayesian framework. Methods: Part 1 of the MIA comprised a control meta-regression using aggregate data on control response over time from randomised studies and a national myasthenia gravis (MG) registry. In Part 2, a combined Bayesian analysis of individual patient-level data from the phase II (NCT03315130), RAISE (NCT04115293) and RAISE-XT (NCT04225871) studies of zilucoplan was conducted using posterior distributions from Part 1 as informative priors. Population mean treatment effect in the change from baseline (CFB) at week 24 in MG-Activities of Daily Living (MG-ADL) and quantitative MG (QMG) scores for zilucoplan versus control were assessed. Results: At week 24, the predicted mean CFB in MG-ADL score was −4.55 (95% credible interval: −6.04, −3.13) with zilucoplan versus −2.00 (−3.35, −0.64) with control (difference: −2.55 [−3.76, −1.40]). The probability of a favourable treatment effect as measured by MG-ADL score at week 24 with zilucoplan versus control was >99.9%. There was an 82.8% probability that the difference in the predicted mean CFB in MG-ADL score at week 24 was greater than the clinically meaningful threshold (⩾2.0-point improvement). Comparable results were observed with QMG. Conclusion: This MIA demonstrates the maintenance of efficacy with zilucoplan versus control up to 24 weeks. Through combining real-world evidence with data from randomised studies, this novel method to estimate long-term treatment efficacy facilitated reduced exposure to placebo in the phase III RAISE study. This methodology could be used to reduce the length of future placebo-controlled studies.